Lifelong Learning and Development for Social Workers - Budayová, Zuzana; Svoboda, Michal; Kóša, Marek; Tudose, Catalina; Molchanova, Irma Igorevna (Journal of Education Culture and Society, 2022)
Aim. In the paper, the authors demonstrate the influence of the education and educational level of social workers on the quality of social work as a profession that helps people in unfavorable situation. They point to the importance of lifelong learning, which is essential for advancing the knowledge and competences of social workers in practice. Concept. Lifelong education for social workers is currently a necessity for their functioning not only on the basis of the rapid, dynamic changes in their problems and social clients, but also for rapid and dynamic changes in the use of methods and techniques of social work. Method. The study deals with the educational development of employees in the profession of social worker. It defines and identifies forms of continuous education of social workers, which can have different methods and which can result in different competencies of a social worker. Results. The study confirms that the lifelong learning of social workers requires constant access to support and information about education, but also to set opportunities and thus facilitate access to the education of social workers. It is necessary to realise that the competences of the social worker must be in accordance with the education that the social worker has. Conclusion. The scientific articles and contributions that we offer in this study point to lifelong learning, which has the effect of expanding the possibilities of a social worker’s work with several types of clients, increases his competences and thus acquires a lot of knowledge and skills that are subsequently applied in practice.